CONTINUITY AND CHANGE INTEGRASI SISTEM PENDIDIKAN PERGURUAN TINGGI PESANTREN - Ach. Nurholis Majid; Khafid Iriyanto; Izzat Amini (Institut Dirosat Islamiyah Al-Amien Prenduan, 2021)
The discourse of integration is a necessity in the educational process. Several Islamic boarding schools have carried out this integration process, with the Al-Amien Prenduan Sumenep Islamic Dirosat Institute as a university in the Al-Amien Prenduan Islamic boarding school environment. This study aims to describe (1) the pattern of educational integration in IDIA Prenduan. (2) continuity and changes in the integration of the higher education system and Islamic boarding school education at IDIA Prenduan. This research approach is qualitative with a case study type. Data collection is carried out through interviews, observations, and documentation. The existing data are then interactively analyzed by Miles & Huberman models. Test the validity of the data through source triangulation and technique triangulation. This research resulted in two conclusions (1) integration patterns in IDIA Prenduan Sumenep, including educational curriculum, student activities, and institutional management. Then, the integration gives birth to consequences of continuity and change. (2) Continuity and change; systems that experience continuity are leadership values, the application of boarding education formats, and the merging of the TMI curriculum and the college curriculum. Meanwhile, changes occurred in intensive institutional positions, changes in the status of universities and the increase of study programs, the increase in lecture programs in universities, and changes in the functions of rectors in the structure.